Corrosion Monitoring Technologies for Reinforced Concrete Structures: A Review - SHEHADEH, KHADIJA (2023)
Reinforced concrete (RC) structures are susceptible to many problems which would lead ultimately to the degradation of RC structures or a total loss in the worst-case scenario. Corrosion represents one of the main degradation sources. Due to the vital impact size of corrosion of RC structures in the form of high maintenance demand and an increase in the total life cycle cost, corrosion monitoring, early detection, and timely remediation is considered a necessity and a crucial proactive measure to control corrosion and limit its impact. In this work, the main classifications of corrosion monitoring systems were explored, highlighting their features, advantages, disadvantages, and future recommended works. To achieve that a state-of-the-art literature review was employed. Six main categories were identified from the literature: visual inspection, electrochemical methods, elastic wave methods, electromagnetic methods, fiber optic sensing methods, and mechanical methods. The subcategories of each of these were reviewed highlighting its concepts, pros, cons, and outlook and future works. Irrespective of the adopted processes for corrosion monitoring, it was concluded that none of these methods represent an optimum solution by itself, where employing a combination of multiple systems is one way of optimizing its results. New technology, algorithms, data processing, and AI are new approaches to improving corrosion monitoring processes. However, it needs further development and research.